Optofluidic rotation of living cells for single-cell tomography - Kolb, Thorsten; Albert, Sahradha; Haug, Michael; Whyte, Graeme (Journal of Biophotonics, 2014)
Flow cytometry provides a high throughput, multi-dimensional analysis of cells flowing in suspension. In order to combine this feature with the ability to resolve detailed structures in 3D, we developed an optofluidic device that combines a microfluidic system with a dual beam trap. This allows for the rotation of single cells in a continuous flow, around an axis perpendicular to the imaging plane. The combination of both techniques enables the tomographic reconstruction of the 3D structure of the cell. In addition this method is capable to provide detailed 3D structural data for flow cytometry, as it improves the reconstructed z-resolution of a standard microscopy system to produce images with isotropic resolution in all three axes.
EAM Import::2019-03-08